Psychosis Associated with Chronic Subdural Hematoma. (April 2022) - Syed, Shahan; Ingram, Kristofer
Abstract: Introduction: Subdural hematoma (SDH) is a diagnosis characterized by a wide array of symptoms. In the absence of apparent neurological deficits, behavioral abnormalities alone make SDH a difficult diagnosis. Chronic subdural hematoma presents with alteration in sensorium, raised intracranial pressure, and motor weakness. Depending on the degree of cerebral compression and location, convulsions or personality changes can also be seen. Common psychiatric manifestation with CSDH is a cognitive impairment which may mimic delirium or dementia. We report a case of an elderly male with no prior psychiatric history who developed insidious psychotic symptoms. Case Presentation: Patient is an 83-year-old male with no prior psychiatric history brought in by police for making suicidal and homicidal threats to family members with increasingly aggressive behavior. He later endorsed a 3-week history of depression symptomatology related to a recent motor vehicle accident. Prior history of chronic myeloid leukemia, hypertension, and hypercholesterolemia with an unremarkable family and social history. On evaluation, the patient was uncooperative, irritable, and verbally aggressive. Laboratory testing, EKG, and MMSE were performed and grossly normal. Noncontrast head CT demonstrated bilateral chronic subdural hematomas. The patient refused neurology consult and proposed interventions but was compliant with risperidone 0.5 mg twice daily. His delusions and aggressive behavior improved drastically and was discharged. Discussion: Chronic Subdural Hematoma (CSDH) is amongst the most common neurosurgical conditions in the United States with an incidence of 10 per 100, 000 annually. Risk factors for CSDH include age, male gender, trauma, coagulopathy, chronic alcoholism, vascular malformations, and metastatic tumors. Noncontrast head CT is diagnostic for CSDH, but MRI should be considered in acute ischemia, infection, or dural-based neoplasms. The DSM-5 criteria for Psychotic Disorder Due to Another Medical Condition include prominent delusions that are the direct pathophysiological consequence of another medical condition and cause clinically significant distress or impairment in social, occupational, or other important areas of functioning. The diversity in symptoms is correlated with increased ICP caused primarily by the ruptured bridging veins. Traditional management of CSDH has been trephination, however, nonsurgical options are available including high-dose corticosteroids to inhibit the formation of new blood vessels thereby reducing mortality. Recurrence is possible and may constitute surgical obliteration of the subdural space. Conclusion: Chronic subdural hematoma should be considered in the differential diagnosis of new-onset psychosis, particularly in patients with other risk factors. A thorough history and physical are vital to ascertain this diagnosis and noncontrast head imaging is confirmatory. Management varies based on the etiology of the CSDH. Funding: No funding